(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
Sheep in Bangladesh are well known as efficient users of low quality roughages, welladapted to hot and humid agro-climatic conditions, capable of bi-annual lambing withmultiple births and resistant to common prevalent diseases. They play an important role inthe supply of animal protein. Present study aimed to investigate possible association ofGDF9 gene polymorphisms with litter size. A total of 126 DNA samples extracted from theblood of indigenous sheep from 5 locations namely Tangail, Noakhali, Naogaon,Gaibandha and Satkhira with known litter size were used to study the association ofGDF9 polymorphism by PCR based RFLP method. Two polymorphic regions of GDF9(FecG1 and FecG8) were amplified by PCR, digested with respective restriction enzymesand 126 sheep were genotyped. Current study revealed that genotype and allelefrequency for FecG1 varied among the sheep from different locations. The genotype (GG,AG, AA) frequency were 51.59%, 45.24% and 3.17% and the allele (G and A) frequenciesin the overall population were 74.21% and 25.79%, respectively. There was a significantassociation of FecG1 of GDF9 gene polymorphism with litter size. The homozygous GGgenotype had the lowest litter size (1.59±0.09; n=65) and homozygous AA genotype hadthe highest litter size (2.00±0.41; n=4). No genotypic variations were found for FecG8.Findings of this study specially the polymorphism of FecG1 together with genotyping ofsome sheep could be utilized in the selection program to increase the lamb productionpotentiality of indigenous sheep of Bangladesh. Res. Agric., Livest. Fish.7(2): 283-292, August 2020